Partnership Living Arrangements of Immigrants and Natives in Germany - Kuhnt, Anne-Kristin; Krapf, Sandra (Frontiers in Sociology, 2020)
This paper compares the partnership arrangements of Turkish and Ethnic German immigrants (i.e., return migrants from Ethnic German communities from predominantly Eastern European countries), the two largest migrant groups in Germany, and native Germans. Most existing analyses of migrants’ partnerships focus on intermarriage, marriage formation, or union dissolution. We know only a little, however, about the prevalence of nonmarital living arrangements. Given that single person households and cohabitation are widespread phenomena mainly in post-materialist societies, analysing whether immigrants engage in these behaviours sheds light on potential adaptation processes. The analyses are based on the German Microcensus of the years 2009 and 2013, with a focus on adults in the 18-40 age group. First, we present descriptive findings on the prevalence of partnership arrangements of immigrants and native Germans. Second, we estimate cross-sectional regressions with the partnership arrangement as the outcome variable in order to control for compositional differences between immigrant groups with respect to education. Our results show that while the vast majority of first-generation immigrants are married, the share of married natives is considerably smaller. Living in an independent household without a partner and cohabitation are rare phenomena among immigrants. By contrast, about one in seven natives is cohabiting and more than one quarter is living in an independent household without a partner. The most prevalent partnership living arrangement of the Turkish second generation is living in the parental household without a partner. These results are robust after controlling for education, age, and year in the multiple regression analysis.